MODEL PEMBERDAYAAN LEMBAGA PERKREDITAN DESA (LPD) SEBAGAI SUMBER PENDANAAN USAHA MIKRO KECIL MENENGAH (UMKM) DI KABUPATEN GIANYAR - Ni Luh Putu Wiagustini; I Gusti Bagus Wiksuana; Desak Ketut Sintaasih; Ida Ayu Nyoman Saskara (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2014)
This research is aimed to indentify the defining variables of the success of Village Installment Institution and composing the empowerment strategy and work plan as founding source of Middle and Micro Business. 142 Village Installment Institutions in Gianyar Regency are taken as samples in this research. They are taken based on their performance by using Stratified Random Sampling. In addition, SWOT (Strength, Weakness, Opportunity, and Threat) is used as the analysis tool in this research. Based on the result of analysis, it is found that recently, Village Installment Institution in Gianyar Regency has strong competitive quality and middle attractive quality. The suggested strategies to improve the competitive and attractive quality as Middle and Micro Founding Institution are Growth and Build strategy. The strategy covers the market penetration strategy-active improvement by using pick up system to middle and micro business in its area, and product development – as middle and micro business founding source by using profit sharing